Three essays on money arguments and financial behaviors - Cumbie, Julie A. (Kansas State University, 2012)
This dissertation explores financial behavior outcomes based on economic, relational, and behavioral characteristics within marriages and individually. Data for the three essays are obtained from the National Longitudinal Survey of Youth 1979 cohort (NLSY79) and the NLSY79 Child and Young Adult (1986-2008) survey. Essay one examined the determinants of money arguments within marriage utilizing Lundberg and Pollak’s (1994) theory of non-cooperative game theory. Respondents’ negative financial behaviors, higher income, and birth order (being laterborn) were found to influence a greater frequency of money arguments. Essay two examined the predictors of individuals’ financial behaviors, specifically socialization characteristics and gender role attitudes (traditional versus non-traditional). Using a theoretical framework of gender role theory (Eagly, 1987), younger age, not being married, being non-Black, non-Hispanic, being males, and having higher income were all found to be predictive of at least of one of the three financial behaviors used in this study. Finally, using a theoretical framework of Becker’s (1993) theory of human capital, essay three explored the intergenerational transfer of attitudes and human capital across two generations and their possible link to the respondents’ financial behaviors. Results showed that mothers’ enhanced human capital, endowed and attained, and nontraditional gender role attitudes have a significant positive impact on the children’s financial behaviors. Respondents’ income was also found to be significant. Combined results of the dissertation reveal that a link exists between the three issues discussed in the individual papers. Essay one examined what factors, including financial behaviors, might influence spousal money arguments. In response, essays two and three explored the predictors of financial behaviors within one generation and across two generations. These studies may be beneficial to financial planners, counselors, and therapists by exposing specific determinants of positive versus negative financial behaviors. These findings also provide useful information for policymakers in creating programs that best serve the needs of individuals related to their personal financial issues. Overall, by exploring not only monetary, but attitudinal and socialization effects of financial behaviors, this study adds to the body of knowledge related to the encompassing field of personal financial planning.
Keywords: Financial behaviors; Gender Studies (0733); Home Economics (0386)